Spatial modulation MIMO systems with dual-polarized antennas - Zafari, Golara. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
In wireless communication systems, multiple-input multiple-output (MIMO) systems have been widely used during the past decades to achieve better performance. However, there is an inevitable issue due to the usage of multi-antennas, which is known as inter-channel interference. Not only inter-channel interference, but also correlation, which is the result of inter-antenna spacing, deteriorate the performance. A promising solution to combat with these issues is to increase inter-antenna spacing or alternatively using orthogonal polarization and decrease the number of channels to eliminate inter-channel interference using spatial modulation (SM). In this work, we address the e ect of dual-polarized antennas over MIMO system employing SM. The performance is evaluated for the general Rician channel with transmit and receive correlation. The equilibrium points, where dual-polarized and uni-polarized channels achieve the same performance, is derived in terms of exact performance as well as Cherno bound and the equilibrium points are compared with the equilibrium points, where dual-polarized and uni-polarized systems have the same ergodic mutual information. It is theoretically shown that two cross points are the same in the Rayleigh scenario, where the number of transmit and receive antennas is equal. Later on, the results are extended to the case where there is channel estimation error and also generalized-SM (G-SM) where more than one antenna is used to transmit the same symbol and achieve diversity gain.
Keywords: MIMO systems.